Effects of soil temperature, seeding depth and seeding date on rhizoctonia seedling blight and root rot of chickpea - Chang, K.F.; Hwang, S.F.; Gossen, B.D.; Turnbull, G.D.; Howard, R.J.; Blade, S.F. (2004)
Effects of soil temperature, seeding depth, and seeding date on rhizoctonia seedling blight and root rot of chickpea. Rhizoctonia solani Kühn, a prevalent fungal pathogen in cultivated prairie soils, can be an important factor affecting seedling establishment of chickpea (Cicer arietinum L.). Studies were undertaken to determine the impact of different soil conditions on seedling establishment, development of root rot, and productivity of desi (Tyson) and kabuli (Sanford) chickpea plants sown in the presence of R. solani AG-4. The impact of soil and air temperatures and seeding depth was studied under controlled conditions, and the influence of seeding date was investigated at three field sites. The host responded to warm soils by increasing its growth rate, and the pathogen by increasing its virulence. The kabuli cultivar, Sanford, showed greater susceptibility to root rot caused by R. solani than the desi cultivar, Tyson. Root rot and shoot infection levels increased with soil temperature for both cultivars, but reached maximum values at substantially lower temperatures for Sanford. Shoot biomass of infected treatments for this cultivar was substantially lower than the controls, while the biomass of Tyson was affected to a lesser degree. Air temperatures of 17/3 °Cday/night allowed relatively unhindered plant growth, even of the more susceptible cultivar, Sanford, in the presence of R. solani, while warmer and cooler temperatures resulted in high mortality and diminished plant growth in surviving plants. Seedling emergence and seedling dry weight were greater at a seeding depth of 2 cm than at 5 cm for seedlings grown in infested soil. In inoculated field plots, seedling emergence was greatest in treatments seeded in late May to early June compared those seeded in early or mid-May; in noninoculated treatments, both emergence and yield were lower in treatments seeded in late May than at the earlier seeding dates. Seeding date did not affect the occurrence of root rot. Incidence de la temperature du sol, de la profondeur des semis et de la date d’ensemencement sur la fonte des semis par Rhizoctonia et sur le pourridié du pois chiche. Can. J. Plant Sci. 84: 901–907. Rhizoctonia solani Kühn, champignon pathogène courant dans les sols cultivés des prairies, peut nuire considérablement à l’implantation du pois chiche (Cicer arietinum L.). On a donc entrepris des études pour déterminer l’incidence de divers états du sol sur l’enracinement des plantules, ’apparition du pourridié et la productivité des pois chiches desi (Tyson) et kabuli (Sanford) semés en présence de R. solani AG-4. On a vérifié les effets de la température du sol et de l’air et de la profondeur des semis en milieu contrôlé, tandis que l’incidence de la date d’ensemencement a été évaluée sur le terrain à trois endroits. Quand le sol est chaud, la plante pousse plus rapidement , mais l’agent pathogène est plus virulent. Sanford (le cultivar kabuli) est plus sensible au pourridié causé par R. solani que le cultivar desi Tyson. La gravité du pourridié et le degré d’infection des pousses augmentent avec la température du sol chez les deux cultivars, mais atteint le maximum à une température nettement plus basse chez Sanford. La biomasse des pousses infectées de ce cultivar était passablement plus faible que celle des témoins, Tyson étant moins affecté sur ce plan. Une température diurne/nocturne de 17/3 °C permet à la plante de croître relativement sans difficulté en présence de R. solani , meme pour Sanford, qui est plus sensible. Une température plus élevée ou plus basse se traduit par un taux de mortalité accru et une croissance plus lente chez les plants survivants. Le pourcentage de levée et le poids sec des plantules sont plus élevés quand on sème les graines à 2 cm plutôt qu’à 5 cm de profondeur dans les sols contaminés. Dans les parcelles inoculées, le pourcentage de levée est plus élevé quand on sème les graines entre la fin de mai et le début de juin que lorsque les semis ont lieu au début de mai ou au milieu du mois; dans les parcelles non inoculées, le pourcentage de levée et le rendement sont plus faibles quand on sème à la fin de mai plutôt qu’à une date antérieure. La date d’ensemencement n’a aucune incidence sur la manifestation du pourridié.